2016
DOI: 10.1176/appi.ps.201500209
|View full text |Cite|
|
Sign up to set email alerts
|

Severe Mental Illness in LGBT Populations: A Scoping Review

Abstract: Objective There is increasing attention to diversity in psychiatric services and a widespread recognition of the mental health implications of stigma for gender and sexual minority individuals. However, these areas remain markedly underdeveloped in the area of severe mental illness. This review is intended to map out the existing base of knowledge in this area to help inform future research, practice, and policy directions. Method A review of the literature was conducted to answer the question, ‘What factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 37 publications
3
71
0
1
Order By: Relevance
“…Moreover, no paper showed a protective role of SM orientation against ED diagnosis, with only two papers out of seven identifying no difference between the SM population and heterosexual peers. This is in accordance with the Stress Minority Theory and recent literature (Hatzenbuehler & Pachankis, ; Kidd, Howison, Pilling, Ross, & McKenzie, ), which has focused on the vulnerability of the fragile SM population in relation to mental and physical health issues and stigmatization, thus confirming the need for specific research and clinical target.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, no paper showed a protective role of SM orientation against ED diagnosis, with only two papers out of seven identifying no difference between the SM population and heterosexual peers. This is in accordance with the Stress Minority Theory and recent literature (Hatzenbuehler & Pachankis, ; Kidd, Howison, Pilling, Ross, & McKenzie, ), which has focused on the vulnerability of the fragile SM population in relation to mental and physical health issues and stigmatization, thus confirming the need for specific research and clinical target.…”
Section: Discussionsupporting
confidence: 89%
“…Although the studies reviewed had samples which largely identified as heterosexual, the dynamics of LGBTQ (lesbian, gay, bisexual, trans, queer) relationships involve unique considerations. The LGBTQ community is one that finds itself over‐represented among those experiencing an SMI (Kidd, Howison, Pilling, Ross & McKenzie, ). A scoping review found that compared to the general population, LGBTQ individuals have a greater risk of developing SMI, which appears to be associated with discrimination that they face (Kidd et al., ).…”
Section: Community Psychology Values and Sexuality Among Homeless Indmentioning
confidence: 99%
“…The community psychology value of diversity may be crucial to explore solutions that aim to reduce the discrimination faced by LGBTQ individuals. To promote diversity, it is important that mental health service providers are given explicit training and information about gender identity, sexual orientation, and stigmatizing beliefs (Kidd et al., ). Service providers should emphasize the creation of safer and more inclusive spaces and to create policies in shelters and care environments to better support inclusion and diversity.…”
Section: Community Psychology Values and Sexuality Among Homeless Indmentioning
confidence: 99%
See 1 more Smart Citation
“…Stigmatization is highly prevalent internationally, with the majority of populations in many countries demonstrating moderate to high levels of stigmatizing views (Krajewski et al, 2013;Pescosolido, 2013). Stigmatizing beliefs lead to a desire for social distance and discrimination resulting in eroded mental health and a denial of access to a range of community resources (Corrigan & Watson, 2002;Corrigan, Larson, & Ruesch, 2009;Krajewski, Burazeri, & Brand, 2013) with further challenges arising as mental illness-related discrimination intersects with poverty and other stigmatized identities (Kidd et al, 2014;2016a).…”
mentioning
confidence: 99%